The Effect of Arthroscopic Triangular Fibrocartilage Repair on Accompanying Extensor Carpi Ulnaris Tendinitis and Synovitis in Triangular Fibrocartilage Tears - Bezirgan, Uğur; Yoğun, Yener; Özgencil, Bedir; Dursun Savran, Merve; Genç, Aysun; Armangil, Mehmet (Journal of Wrist Surgery, 2023)
Purpose Management of ulnar-sided wrist pain is difficult due to the complexity of the anatomy and the similarity of the signs and symptoms of possible diagnoses. The study's main purpose is to examine the effect of arthroscopic triangular fibrocartilage (TFC) repair on untreated extensor carpi ulnaris (ECU) tendinitis and synovitis.Methods Thirteen patients who underwent arthroscopic TFC repair in our clinic and preoperatively demonstrated ECU tendon pathology with magnetic resonance imaging (MRI) were included in the retrospective study. Pre- and postoperative visual analog scale (VAS), pre- and postoperative tendinitis and synovitis, postoperative Mayo and patient-rated wrist evaluation score, postoperative grip strength of the operated and control sides, short and long diameters of the ECU tendon in ultrasonography were recorded.Results The mean age of 13 patients (9 females and 4 males) was 39.54 ± 13.54, and the mean follow-up period was 26 ± 7.25 months. While there was no significant difference between pre- and postoperative tendinitis or synovitis levels, VAS decreased significantly (8.46 ± 1.33 vs. 3.00 ± 2.31, p = 0.0016). While the grip strength was 21.78 ± 7.83 on the control side, it was 18.28 ± 7.51 on the surgery side, being significantly lower (p = 0.0252). Ulnar variance did not affect tendinitis or synovitis. Short and long diameters of ECU were similar for the operated and control sides. While the short diameter did not affect the synovitis–tendinitis score, the bigger the long diameter, the higher the synovitis score (rho = 0.5162).Conclusion In the presence of ECU, tendon pathologies accompanying TFC lesions, additional surgical interventions are mandatory as arthroscopic TFC repair has no significant effect on the healing of ECU.Level of evidence: 4.
Keywords: extensor carpi ulnaris; synovitis; tendinitis; triangular fibrocartilage; wrist arthroscopy